Case report: Pneumonia with clinical symptoms precedes imaging evidence after immune checkpoint inhibitors combined with radiotherapy in lung squamous cell cancer - Wang, Yao; Wang, Yimeng; Yu, Jinming; Meng, Xiangjiao (Frontiers in Immunology, 2022)
Immune-checkpoint inhibitors (ICI) targeting programmed cell death 1 (PD-1) and its ligand 1 (PD-L1) have quickly changed the treatment landscape in advanced non-small cell lung cancer. However, any patient treated with an immune checkpoint inhibitor is at risk for immune-related adverse events (irAEs). Checkpoint inhibitor pneumonitis (CIP) is a rare but potentially severe pulmonary toxicity of immunotherapy. Since the imaging features and symptoms are not specific, the diagnosis of CIP is challenging. In addition, CIP may mimic other lung diseases. Due to these characteristics, proper patient management may be delayed. So, a comprehensive understanding of imaging features is essential for a prompt detection and correct management of these drug-induced lung diseases. We presented a patient with lung squamous cell cancer who has clinical symptoms preceding imaging evidence of pneumonitis after immunotherapy and radiotherapy. We also discussed the safety of immunotherapy, the complexity and management of immune pneumonitis.